2010
DOI: 10.1016/j.bmcl.2010.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vitro evaluation of N-alkyl-3-hydroxy-3-(2-imino-3-methyl-5-oxoimidazolidin-4-yl)indolin-2-one analogs as potential anticancer agents

Abstract: A series of novel 3-hydroxy-3-(2-imino-3-methyl-5-oxoimidazolidin-4-yl)indolin-2-one analogs (3) have been synthesized under microwave irradiation and conventional heating methods. These analogs were evaluated for in vitro cytotoxicity against a panel of 57 human tumor cell lines. Compound 3o had GI50 values of 190 nM and 750 nM against A549/ATTC non-small cell lung cancer and LOX IMVI melanoma cell lines, respectively, and both 3n and 3o exhibited GI50 values ranging from 2–5 μM against CCRF-CEM, HL-60(TB), K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…1H-indole-2,3-dione derivatives have driven much attention for their bioactivities on anti-HIV [1], anticonvulsant[ 2] and antitumor activities [3,4].Ithas been reported that the introduction of substituents at the Natom of indolin-2-ones enhances their cytotoxicity against avariety of cancer cell lines [5,6]. In an attemptt oo btain compounds that might also exhibit antitumor properties, we carried out the reaction of 6-bromo-1-(2-bromoethyl)indoline-2,3-dione with an excess of morpholine.…”
Section: Discussionmentioning
confidence: 99%
“…1H-indole-2,3-dione derivatives have driven much attention for their bioactivities on anti-HIV [1], anticonvulsant[ 2] and antitumor activities [3,4].Ithas been reported that the introduction of substituents at the Natom of indolin-2-ones enhances their cytotoxicity against avariety of cancer cell lines [5,6]. In an attemptt oo btain compounds that might also exhibit antitumor properties, we carried out the reaction of 6-bromo-1-(2-bromoethyl)indoline-2,3-dione with an excess of morpholine.…”
Section: Discussionmentioning
confidence: 99%
“…1H-indole-2,3-dione and its derivatives demonstrate a broad spectrum of biological and pharmacological activities including anti-cancer activities [1,2]. It has been reported that the introduction of alkyl group or aryl group into the N atom of indolones can significantly increase its cytotoxicity against a variety of cancer cell lines [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…The residue included the prevailing product 5,7-dibromo-1-(2-bromoethyl)indoline-2,3-dione (R f = 0.40, m.p. 375-377 K ; yield 40%) and the title product 5',7'-dibromo-1'-(2-bromoethyl)spiro[ [1,3]dioxolane-2,3'-indolin]-2'-one (R f = 0.5, m.p. 382-383 K; yield 38%).…”
mentioning
confidence: 99%
“…1H-indole-2,3-dione derivatives possess av ariety of biological activities, including antitumor activity [2].I ntroduction of substituents at the 3-and 5-positions of the indolin-2-one ring have recently led to many derivatives possessing more potent antiumor activities [3,4].Inaddition, the introduction of an alkyl group or aryl group at the Natom of indolin-2-ones enhanced their cytotoxicity againstavarietyofcancercelllines [5,6]. Herein, we report thecrystal structure of oneofthe derivateswhich maybea potential anticancer agent.…”
Section: Discussionmentioning
confidence: 99%